Role Of Vihara (Ayurvedic Lifestyle) In The Prevention And Management Of Dermatological Disorders - SATYAPAL SINGH, (International Journal of Pharma and Bio Sciences, 2015)
The main objective of this review article is to increase the awareness regarding Vihara (Ayurvedic lifestyle) in the prevention and management of dermatological disorders and to discuss its impact on physical, mental as well as social health of an individual. The authentic subject material has been reviewed from Ayurveda and modern medical literature. Concerned articles were reviewed from different journals and used as the basis for the discussion of how the Ayurvedic lifestyle affects the physical, mental and social health and help in the prevention and management of dermatological disorders. The concerned material has also been searched on the internet. Ahara (diet) and Vihara are very much emphasized in Ayurvedic system of medicine for the prevention as well as management of a wide range of disorders including dermatological disorders. Vihara includes different types of life style (dos and don’ts) as suggested in Ayurveda. It is well acknowledged that stress is a major factor in the pathogenesis of most of the dermatological disorders like psoriasis, atopic dermatitis etc. Therefore, the lifestyle modification having a holistic approach to promote psychosomatic health should be recommended. Ayurvedic lifestyle promotes physical, mental as well as social health and ultimately leads to symptomatic improvement and improvement in the quality of life and thus help in the prevention and management of dermatological disorders.